Pendampingan Pengajuan Certificate of Origin (CoO)/Surat Keterangan Asal (SKA) untuk Produk Kayu dan Turunannya di Provinsi Kalimantan Tengah Periode Tahun 2025 - Mas Aji Rassya Narendra Raka Suwardi; Naya Deswity Pasha; Bella Bella; Febrianti Febrianti; Rita Yuanita Toendan (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study aims to analyze the assistance process for applying for the Certificate of Origin (CoO) or Surat Keterangan Asal (SKA) and the realization of exports of wood products and their derivatives in Kalimantan Tengah Province in 2025. The study used a descriptive method with a qualitative approach through interviews, observations, and documentation at the Department of Trade and Industry of Central Kalimantan Province. The results showed that the assistance process for submitting SKA was carried out through the electronic e-SKA system, starting from account registration, data entry, document verification, to the issuance of SKA. The assistance provided helped exporters understand submission procedures, reduce data input errors, and accelerate document verification. Based on export realization data in 2025, wood products and their derivatives became leading export commodities with an export volume of 240,795.83 TNE and an export value reaching USD 49,000,166.36. Exported commodities included plywood, veneer, wood pellets, moulding, finger joints, laminated scantling, and chopsticks with major destination countries including Japan, India, South Korea, the Netherlands, China, the United States, and the United Arab Emirates. The obstacles encountered included incomplete supporting documents, data input errors in the e-SKA system, and disruptions in network and electronic systems. Therefore, increased socialization, technical assistance, and optimization of the service system are needed to support the smooth implementation of export activities in Central Kalimantan Province.